Comparison of query caching approaches in P2P networks - Rozlina, Mohamed (Faculty of Computer Systems and Software Engineering, 2011)
This article is comparing query caching implementations on various researches that have been implemented on several peer-to-peer (P2P) routing strategies. Several routing strategies have been compared in the previous chapter. This comparison is aim to foresee the current trend of using caching for query routing in P2P.